Synthesis, structural, and magnetic characterization of a mixed 3d/4f 12-Metallacrown-4 family of complexes - Athanasopoulou, Angeliki A.; Carrella, Luca M.; Rentschler, Eva (Inorganics, 2018)
A new family of complexes (tBu4N)[LnIII(O2CBut)4][12-MC-Mn(III)N(shi)-4]·5CH2Cl2 (Ln = Gd (1) and Tb (2)), (tBu4N)2[YIII(O2CBut)4][12-MC-Mn(III)N(shi)-4](ClO4) (3); where shiH3 = salicylhydroxamic acid; ButCO2 - = pivalate ions; tBu4N = tetrabutylammonium and ClO4 - = perchlorate ions, has been isolated. The reaction of salicylhydroxamic acid with Mn(O2CBut)2·2H2O, Ln(NO3)3·xH2O, tBu4NClO4 in the presence of morpholine (C4H9NO) led to the isolation of compounds 1-3. The complexes belong to the 12-MC-4 family of Metallacrowns (MCs) possessing a central Mn4 IIILnIII(μ-NO)411+ core with the four MnIII atoms occupying the periphery positions, while the formed [Mn-N-O] repeating unit, assists in the accommodation of the LnIII atom in the center of the ring. Peripheral ligation is provided by four η1:η1:μ pivalate ions. Direct current magnetic susceptibility (dc) measurements revealed the presence of predominant antiferromagnetic exchange interactions within the metal centers. A 1-J fitting model was used in order to quantify the MnIII-MnIII interactions and fitting of the data, for the diamagnetic YIII analogue, gave J = -3.74 cm-1 and gMn(III) = 2.07. Fitting of the Mn4Gd compound using a 2-J model, counting additionally for the MnIII-GdIII interactions, revealed values of J1 = -3.52 cm-1, J2 = -0.45 cm-1, and gMn(III) = 1.99.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Coordination chemistry; Heterometallic complexes; Inorganic synthesis; Metallacrowns; Single-molecule magnets (SMMs)